Factors Affecting the Role of State in the context of Digital Transformation of Education in Vietnam - Nhan, Trung Phan (International Journal of Multidisciplinary Approach Research and Science, 2024)
Education 4.0 (EDUC4) is a trend that is completely changing the way of teaching and learning at all levels from preschool, elementary school, high school to university in the 4.0 industrial era. This concept encourages learners to equip themselves with skills and knowledge through virtual learning environments and advanced technologies such as the Internet of Things (IoT) and artificial intelligence (AI). However, to implement EDUC4 effectively and fairly, the role of the state is very important. The state needs to develop supportive policies, invest in technology infrastructure and digital skills training for teachers. Synchronization between policy and practice is a key factor to create a modern, flexible education system that meets the requirements of the Fourth Industrial Revolution. In Vietnam, digital transformation in education is institutionalized in documents from the Prime Minister and the Ministry of Education and Training. The national digital transformation program to 2025, with a vision to 2030, has changed teaching methods from traditional to active, improving the quality of education and saving time. The Ministry of Education and Training has built a database to manage detailed information of all schools from preschool to high school, digitized and connected the education sector database with the national database about population. Although many positive results have been achieved, Vietnam still has many limitations in implementing EDUC4, such as difficulties with network infrastructure in remote areas, control of digital learning materials, and legal regulations. Incomplete. A strong effort from the state is needed to overcome these challenges and ensure that all learners have access to modern and effective education. Through this article, the author provides a qualitative research model from previous studies on factors affecting the role of the state in EDUC4, thereby conducting linear regression analysis and providing solutions suitable recommendations.